Neonatal myocardial infarction in Williams–Beuren syndrome. (June 2019) - Lesmana, Harry; Dyer, Lisa; Morales, David L.S.; Ryan, Thomas D.; Hopkin, Robert J.
Abstract: Williams–Beuren syndrome (WBS) is a contiguous gene deletion syndrome in chromosome 7q11.23, resulting in elastin arteriopathy. Patients with WBS are at higher risk for major cardiovascular events, including sudden death due to structural congenital heart diseases and arrhythmia. Neonatal myocardial infarction is an exceedingly rare presentation of WBS. Here, we report the case of a 2-week-old infant with neonatal myocardial infarction due to severe coronary artery insufficiency. We systematically reviewed published reports of sudden death in WBS and identified an additional 19 cases. Of 10 individuals who had autopsy or direct examination of the heart during cardiotomy, 5 had evidence of myocardial ischemia or infarctions. An additional 2 patients with WBS had evidence of severe coronary insufficiency and myocardial ischemia, as determined by cardiac imaging. In agreement with prior studies, we did not find that degree of supravalvar aortic stenosis or left ventricular outflow tract obstruction were predictors of coronary artery stenosis. Additional aortic valve abnormalities, such as bicuspid aortic valve, may be better predictors of coronary stenosis. Highlights: Two weeks old newborn presented with acute cardiac failure due to myocardial infarction Diagnosing the etiology of acute cardiac failure in newborn period is challenging due to non-specific symptoms Neonatal myocardial infarction could be a presenting symptoms of arteriopathy in newborn with Williams-Beuren syndrome SVAS or LVOTO are not predictors of coronary artery stenosis in patients with Williams-Beuren syndrome